Prototyping of Geolocated Applications with Storyboarding - An Experience Report in the Case of the National Irrigation Information System - Nascimento, Iorrana Maria do; Costa, Heitor Augustus Xavier; Capeleti, Bruna Santana; Malheiros, Neumar Costa; Freire, André Pimenta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
This article discusses the use of storyboarding as a prototyping approach in the presentation of Geographic Information Systems (GIS). The absence of illustrative visual elements in map prototyping and its interactions has resulted in significant challenges in a governmental project. To address this issue, storyboarding was adopted as a concise and visually accessible representation of the developing system. Through storyboarding, users were able to gain a clearer understanding of the proposed functionalities and interactions, facilitating the understanding process and enabling the collection of valuable feedback to enhance the project.